Analysis of agricultural development in Ngringo Village, Kecamatan Jaten, Karanganyar District - Myalida, Ara Shaula; Hapsoro, Hamam Rasendriya; Rahmiantini, Nafisah; Aprilia, Yohana Brenda; Antriyandarti, Ernoiz; Hidayah, Aditya Ramadan Nur (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Agricultural development is crucial for rural economic growth and food security. This study analyzes agricultural development in Ngringo Village, Indonesia, examining potentials, challenges, structural and institutional transformations, technology transfer, and appropriate development models. Previous research has focused on broader regional agricultural trends, while this study provides an in-depth analysis of a specific village undergoing rapid change. Method: The study employed purposive sampling to select Ngringo Village. Data collection involved observations, structured interviews with key informants, and document analysis. Both primary data from village officials and secondary data from government sources were utilized. Findings: Ngringo Village exhibits both physical potential (strategic location, affordable land) and non-physical potential (socio-cultural life, efficient administration). Challenges include limited farmer knowledge of marketing and post-harvest processing. Structural transformation is evident in the shift from agriculture to industrial and service sectors due to urbanization pressures. Institutional transformation has led to the establishment of farmer groups and associations. Technology transfer is occurring, with the adoption of mechanized farming equipment, though digital technologies are not yet fully embraced. Conclusion: The agricultural development model in Ngringo Village aligns with the location model, influenced by its proximity to urban areas. Ngringo Village is undergoing significant agricultural transformations driven by urbanization and industrialization. While facing challenges in land conversion and marketing, the village demonstrates resilience through institutional adaptations and selective technology adoption. Novelty/Originality of this article: This study proposes an integrated digital platform for sustainable agricultural development. The platform connects farmers to markets, provides online training, and facilitates stakeholder collaboration, adaptable to different peri-urban contexts across the country.